Theater and Film - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see a variety of examples of how music can be theatrical, as well as some ways in which music is used in films - - Discover common threads that link musical theater, opera, show choirs, marching bands, and films - - Enjoy a silent film clip with organ music background, and learn how music can set the mood for a film - - Watch musical puppet theater from Korea and Australia.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - Questions to Encourage Critical Thinking - - Correlations with THE MUSIC CONNECTION - - Student Follow-up - - Vocabulary - - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Music in the theater; Motion picture music; Films for the hearing impaired